1999
DOI: 10.1093/emboj/18.9.2621
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the maize gene crp1 reveals similarity between regulators of mitochondrial and chloroplast gene expression

Abstract: The maize nuclear gene crp1 is required for the translation of the chloroplast petA and petD mRNAs and for the processing of the petD mRNA from a polycistronic precursor. In order to understand the biochemical role of the crp1 gene product and the interconnections between chloroplast translation and RNA metabolism, the crp1 gene and cDNA were cloned. The predicted crp1 gene product (CRP1) is related to nuclear genes in fungi that play an analogous role in mitochondrial gene expression, suggesting an underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
232
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(237 citation statements)
references
References 56 publications
5
232
0
Order By: Relevance
“…The yeast PET309 and the Neurospora CYA-5 PPR proteins are necessary for the maturation and/or accumulation of coxI mRNA and its translation (Coffin et al, 1997;Manthey et al, 1998). The maize crp1 PPRcontaining gene product is required for processing of the petD transcript and for the translation of petA and petD mRNAs (Fisk et al, 1999). Another maize PPR gene is required for the accumulation of plastid ribosomes (Williams and Barkan, 2003).…”
Section: Ppr-containing Fertility Restorers Are Members Of a Large Gementioning
confidence: 99%
See 1 more Smart Citation
“…The yeast PET309 and the Neurospora CYA-5 PPR proteins are necessary for the maturation and/or accumulation of coxI mRNA and its translation (Coffin et al, 1997;Manthey et al, 1998). The maize crp1 PPRcontaining gene product is required for processing of the petD transcript and for the translation of petA and petD mRNAs (Fisk et al, 1999). Another maize PPR gene is required for the accumulation of plastid ribosomes (Williams and Barkan, 2003).…”
Section: Ppr-containing Fertility Restorers Are Members Of a Large Gementioning
confidence: 99%
“…Mutants in the Arabidopsis hcf152 PPR gene exhibit high chlorophyll autofluorescence and have defects in the processing and/or stabilization of transcripts of the psbB-psbT-psbH-petB-petD operon (Meierhoff et al, 2003). In the chloroplast stroma, maize CRP1 has been found in a large complex of unknown composition (Fisk et al, 1999), in contrast to Arabidopsis HCF152, which is not found in a high molecular mass complex (Meierhoff et al, 2003).…”
Section: Ppr-containing Fertility Restorers Are Members Of a Large Gementioning
confidence: 99%
“…The coding sequence of mature Zm-APO1 (i.e., lacking its predicted chloroplast targeting sequence) was amplified from our maize leaf cDNA library (inbred line B73) (Fisk et al, 1999) using primers oAPO1for and oAPO1rev (see Supplemental Table 3 online) and Phusion DNA polymerase (New England Biolabs). The PCR product was digested with BamHI and SalI and cloned into the pMAL-TEV vector as previously described for RNC1 .…”
Section: Expression and Purification Of Recombinant Zm-apo1 And At-apo1mentioning
confidence: 99%
“…A few functions have been identified, such as those that enable the restoration of cytoplasmic male fertility (Bentolila et al, 2002;Brown et al, 2003;Desloire et al, 2003;Kazama and Toriyama, 2003;Koizuka et al, 2003;Laforest et al, 2003;Akagi et al, 2004;Komori et al, 2004;Klein et al, 2005) and organelle biogenesis (Barkan et al, 1994;Fisk et al, 1999;Hashimoto et al, 2003;Yamazaki et al, 2004;Kotera et al, 2005).…”
Section: Introductionmentioning
confidence: 99%